Impacts of the US CDC recommendation on human papillomavirus vaccine uptake, 2010–2015 - Ghosh, Pallab K.; Chaudhry, Ahmed; Campbell, Janis E.; Kim, Myongjin; Smith, Kyle; Demir, Firat; Zhao, Junying (Frontiers in Public Health, 2024)
ObjectivesAs one type of vaccine policy, the effectiveness and spillover effects of the US CDC vaccine recommendations are inadequately evaluated. This study aims to fully evaluate its impacts on male adults, in addition to children, using better data.DesignA before-after study design to examine the CDC’s 2011 HPV vaccine recommendation for men aged 11–21.Data analysisIndividual-level data included the 2010–2015 US National Health Interview Survey full sample of 7,000 male children aged 11–18, younger adults aged 19–21 and 22–25, and older adults aged 26–60. Pooled cross-sectional surveys contained individual-level vaccination, socioeconomic, and demographic information. Outcome variable is an individual HPV vaccination status, measured as individual probability of HPV vaccination. Dummy regressions were estimated by a Linear Probability Model (LPM) with fixed effects for target and non-target age groups.ResultsThe policy was significantly associated with a 14.8% (p < 0.001) increased individual likelihood of HPV vaccination for men aged 11–21. It was also associated with a modest spillover effect, a 5.6% (p < 0.001) increased individual likelihood for men aged 22–25 and marginally for men aged 26–60. African American men and men with poor health were 2.7 and 15.4% less likely to uptake HPV vaccines than white men and men with good or fair health, respectively.ConclusionThis study complements the existing policy evaluation literature on HPV vaccine recommendation among male children by including adults and using better data. Findings offer comprehensive evidence of the effectiveness and spillover effects of this recommendation type of federal-level policy, provide policy lessons for other vaccines, and identify vulnerable subpopulations as targets for future policies.